Multi-decadal aspen dynamics show recruitment bottleneck across complex mountain community - Stoddard, Michael T.; Rodman, Kyle C.; Crouch, Connor D.; Huffman, David W.; Fulé, Peter Z.; Waring, Kristen M.; Moore, Margaret M. (Forest ecology and management, 2024)
Changes in forest structure and shifts in tree species composition have occurred globally due to climate change and altered disturbance regimes. With climate trending toward warmer and drier conditions, these altered forest communities may reorganize in diverse and unpredictable ways. This is especially true in mountain environments where a range of vegetation types and abiotic conditions coexist. In this study, we used long-term permanent plot data from a site spanning broad environmental gradients to assess regeneration and mortality patterns in populations of aspen (Populus tremuloides). The study site, located on the San Francisco Peaks, Arizona, USA, is near the hot, dry edge of the species’ range and has experienced compounding pressure from extreme drought, chronic ungulate browsing, and wildfire in the past two decades. Over a 20-year study period, spanning one of the most prolonged drought periods in at least 1200 years, aspen overstory mortality averaged 42 % and was most common in smaller, younger trees and at lower elevations. Aspen regeneration density increased 13 % and was found in a greater proportion of study sites. However, we observed a noticeable lack of stems in the tallest regeneration size class (>200 cm) and the smaller tree size class (2.5–15 cm in diameter), potentially indicating a demographic bottleneck whereby few trees are recruiting into the overstory. Likewise, prolific aspen suckering occurred after a 2001 wildfire, although regeneration density eventually decreased to pre-fire levels, with <1 % of individuals reaching heights >200 cm. Aspen regeneration densities showed the greatest increases in cool, wet sites and beneath open forest canopies. Disturbances function as catalysts for aspen regeneration, but persistence of aspen stands depends on recruitment of stems into overstory size classes, a process that is limited, particularly on lower and more exposed sites. •Multi-decade evidence of aspen changes across mountainous environment.•Significant aspen mortality especially in young and lower-elevation trees.•Despite increased aspen regeneration, notable lack of recruitment into mature size classes.•Aspen regeneration showed the greatest increases in cool, wet sites and beneath open forest canopies.